Globalization and public administration - Ali Farazmand (1999)
This article discusses globalization and its implications for public administration. Using a political economy approach, an analysis is made of the different meanings and perspectives of globalization, of the causes and consequences of globalization, and of the underpinnings or constitutive elements of globalization, a phenomenon that is all-embracing with transworld and far-reaching implications for society, governance, and public administration. Causes of globalization are discussed, such as the economic factors of surplus accumulation, corporate reorganization, shift of corporate power structure, global money and financialization, global state and administration, domestic decline, rising human expectations, innovations, and global supranational organizations such as the United Nations. Consequences of globalization are discussed, including the positive impact such as continuity and persistence of the state and public administration, but also its negative consequences such as threat to democracy and community, increasing corruption, and elite empowerment. Then a discussion is made of the converging, hegemonic global order with a question of possible counter-hegemonic model that might alter the dominant world order. Finally, the article presents a number of significant implications - positive and negative - for public administration as a theory and practice, from both American and comparative/international perspectives. - Reproduced
Keywords: Globalization; Public administration